2018
DOI: 10.6002/ect.2017.0232
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Sexually transmitted diseases may occur more frequently in sexually active asymptomatic renal transplant recipients than in nontransplanted individuals. Real-time multiplex polymerase chain reaction analysis may be a suitable method for determining these pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In a study by Sarier et al, 80 sexually active asymptomatic kidney transplant recipients were screened with vaginal or urethral swabs and urine samples, and findings were compared to 80 healthy controls. 5 The prevalence of Gardnerella vaginalis and Ureaplasma species were significantly higher among the transplant population, whereas no difference was found in other findings. Of note, no cases of N. gonorrhoeae or C. trachomatis were detected among the transplant patients.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In a study by Sarier et al, 80 sexually active asymptomatic kidney transplant recipients were screened with vaginal or urethral swabs and urine samples, and findings were compared to 80 healthy controls. 5 The prevalence of Gardnerella vaginalis and Ureaplasma species were significantly higher among the transplant population, whereas no difference was found in other findings. Of note, no cases of N. gonorrhoeae or C. trachomatis were detected among the transplant patients.…”
Section: Discussionmentioning
confidence: 68%
“…Of note, no cases of N. gonorrhoeae or C. trachomatis were detected among the transplant patients. 5 In a retrospective study by Ashoor et al including 49 pediatric transplant patients above the age of 13, STIs were recorded in 4/13 sexually active patients with a higher frequency in female patients. 6 One possible explanation to the lower incidence of STIs among kidney transplant patients compared to the general population is the high comorbidity among transplant patients that may result in sexual dysfunction and lower likelihood of being sexually active.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for Mycoplasma hominis infections are found to be less common than Ureaplasma infections. In a study performed by Sarier et al reported that Mycoplasma hominis infections occur mainly in severely immuno suppressed patients 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on outcome, kidney transplantation is the most effective method for the treatment of end-stage renal disease [1]. Due to a shortage of cadaveric organs, living-donor kidney transplantation is becoming more common [2].…”
Section: Introductionmentioning
confidence: 99%